Farmers’ perceptions on the capacity of extension practitioners on climate change in the Eastern Cape Province of South Africa - Makamane, Anathi; Loki, Olwethu; Swanepoel, Jan; Zenda, Mashford; Van Niekerk, Johan (Frontiers in Climate, 2025)
Farmers expect agricultural extension practitioners to provide and effectively communicate knowledge on climate-resilient agricultural practices and their impacts. In the face of increasing climate variability, extension services are crucial in equipping farmers with strategies for adaptation and mitigation. However, the effectiveness of these services in improving farm level adaptation remains limited. This study utilized a cross-sectional survey with 175 randomly selected farmers, employing interviews and structured questionnaires for data collection. Farmers’ perceptions of extension practitioners’ competencies were analyzed through content analysis, while a binomial logistic regression model identified factors influencing these perceptions. The findings revealed that most farmers accessed extension services and relied on them for climate adaptation information. Approximately 72.6% of respondents viewed practitioners as knowledgeable, positively influencing their adaptation efforts. However, significant differences in perception emerged: male and female farmers evaluated practitioners differently, and experienced farmers were more critical of practitioners’ climate competencies. Membership in farmer organizations correlated with more favorable perceptions, while limited access to extension services was associated with less positive views, highlighting access barriers. Observed climate changes include floods (53%), prolonged droughts (63.4%), very hot seasons (25%), and very wet seasons (22%), while 3.7% of respondents reported no observed changes. Farmers emphasized the importance of technical climate knowledge among practitioners and the need for continuous training to enhance their effectiveness. The study recommends fostering regular farmer-practitioner engagement, prioritizing ongoing technical training for extension officers, and incorporating indigenous knowledge systems into extension frameworks to address local adaptation needs effectively.